Open aneurysm repair in patients with concomitant abdominal aortic aneurysm and aorto-iliac occlusive disease is associated with a high mortality and surgical complication rate (Swiss Medical Weekly, 2021)
AIM OF THE STUDY: To evaluate whether the outcome after open aneurysm repair combined with aorto-femoral bypass in patients with concomitant abdominal aortic aneurysm (AAA) and aorto-iliac occlusive disease (AIOD) is inferior to open aneurysm repair for isolated AAA or aorto-femoral bypass for isolated AIOD.METHODS: We performed a retrospective analysis of 30-day mortality, 1-year mortality and surgical complications of consecutive patients undergoing elective aneurysm repair, aorto-femoral bypass or a combination of these at two vascular surgery departments from 2003 to 2013. Potential risk factors were investigated by multivariable analysis.RESULTS: Overall, 511 patients underwent open repair for isolated AAA, 104 aorto-femoral bypass for isolated AIOD and 46 open AAA repair combined with aorto-femoral bypass for concomitant AAA and AIOD. Surgical complications occurred in 17% of AAA, 23% of AIOD and 37% of combined patients (odds ratio [OR] combined vs AAA 2.76, 95% confidence interval [CI] 1.43–5.34; p = 0.003). Colon ischaemia occurred in 3.7% of AAA, 2.9% of AIOD and 13% of combined patients (incicidence rate ratio [IRR] combined vs AAA 3.27, 95% CI 1.37–7.81; p = 0.01). The 30-day mortality was 3.1% in AAA, 4.8% in AIOD, and 11% in combined patients (IRR combined vs AAA 3.17, 95% CI 1.26–7.96; p = 0.01). One-year mortality was 5.7% in AAA, 5.8% in AIOD and 15% in combined patients (IRR combined vs AAA 2.50, 95% CI 1.17–5.35; p = 0.02).CONCLUSIONS: Combined AAA repair and aorto-femoral bypass has a significantly higher 30-day mortality and postoperative complication rate than isolated AAA repair. Patients with concomitant AAA and AIOD thus represent a high-risk population, which should be considered when deciding on the indication for AAA treatment.